Effect of Low Impact Aerobic Exercise on Functional Balance and Quality of Life in Type 2 Diabetes Mellitus Patients. - Peni Hardjanti; Bayu Santoso; Nuniek Nugraheni; Agung Pranoto (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: To determine the effect of low impact aerobic exercise on functional balance and the quality of life in type 2 Diabetes Mellitus (DM) patientsMethods: This is an experimental study. Participants were recruited from outpatient Diabetes Clinic in Dr. Soetomo General Hospital, Surabaya, Indonesia. Subjects of this study are men and women aged 30-70 years whose diagnosed with type 2 DM, with A1c less than 10%, have been using oral anti diabetic drug or subcutaneous insulin less than 30 IU daily, blood glucose level before exercise less than 250mg%, and Berg Balance Scale between 41-56. Subjects were randomized into 2 groups with 38 subjects in the exercise group and 37 in the control group. The exercise group followed 25-30 minutes diabeticaerobic low impact exercise 3 times a week for 3months, while the control group did not. Functional balance and quality of life before and after exercise were assessed using Berg Balance Scale (BBS) andthe Sickness Impact Profile (SIP) questionnaire. Difference in BBS and quality of life improvement measured by SIP questionnaire were analyzed after 3 months of exercise.Results: Mann Whitney test showed significant difference of the total score of BBS in the exercise group (p 0.02; α < 0.05). Chi Square test revealed significant improvement in four of the twelve parameters ofthe quality of life: sleep and rest (SR) (p 0.044), body care and movement (BCM) (p 0.017), ambulation (A) (p 0.001), and work (W) (p 0.000) in the exercise group.Conclusions: Low impact aerobic exercise in type 2 Diabetes Mellitus patients may improve functional balance and the SR, BCM, A, and W parameters of the quality of life.Key words: Low impact aerobic exercise, type 2 diabetic mellitus, functional balance, quality of life.